Is Holland a Lumpy Country? An Application of the Lens-Condition to Dutch Cities - Steven Brakman; Tijl Hendrich; Charles van Marrewijk; Jennifer Olsen (Center for Economic Studies and ifo Institute (CESifo), 2021)
Traditional trade theory assumes that countries are dimensionless points. Recent research shows, however, that the internal geography of countries is important for the effects on trade. One aspect of internal geography is the uneven spatial distribution of factors of production. Factors of production especially concentrate in urban locations. The so-called lens-condition tests whether the (urban) distribution of factors of production is uneven enough to affect the national structure of trade. Using detailed data and applying the condition to 22 cities and 4 regions within The Netherlands for 2007-2017, shows that the condition is fulfilled. We explain why.
Keywords: F10; 330; lumpiness of countries; HOS model